A quantitative risk assessment for the onward transmission of highly pathogenic avian influenza H5N1 from an infected small-scale broiler farm in Bogor, West Java, Indonesia - de Glanville, Will; Idris, Syafrison; Costard, Solenne; Unger, Fred; Pfeiffer, Dirk (International Food Policy Research Institute, 2010)
Highly pathogenic avian influenza (HPAI) H5N1 is endemic in Indonesia, where it is an important cause of disease in commercial, semi-commercial and backyard poultry flocks. It is likely that small-scale broiler farms, which typically have poor biosecurity practices together with large populations of susceptible birds, play an important role in the spread of the disease in the country. This report describes a quantitative risk assessment that was conducted to describe the risk of transmission of the HPAI virus (HPAIV): a) between small-scale broiler farms, and b) between small-scale broiler farms and backyard poultry flocks. For this study we focus in particular on the District and Municipality of Bogor, West Java, Indonesia.